Foundational mathematical knowledge of prospective teachers: Evidence from a professional development training - Mukuka, Angel; Alex, Jogymol K. (Pythagoras (Pretoria, South Africa), 2024)
This study examined the effect of a professional development training programme on 20 second-year preservice mathematics teachers’ knowledge in foundational mathematical concepts at a rural university in South Africa. The training programme aimed to enhance preservice teachers’ mathematical knowledge for teaching. An embedded mixed-methods case study design was employed. Baseline and endline assessments were administered before and after the training. A participant feedback survey was also administered after the training. Results showed that the training significantly improved the preservice teachers’ understanding and confidence in the selected concepts, despite their low baseline scores. The participants also expressed satisfaction with the knowledge they gained and appreciated the integration of theory and practice in the training. These findings suggest the need for teacher training institutions to ensure that preservice teachers are well versed in both university-level and school-level mathematics. They also support the need for collaboration with other stakeholders to provide preservice teachers with relevant and engaging professional development opportunities that can enhance their mathematical knowledge for teaching.\r\n\r\nContribution\r\nFindings of this study point to a renewed emphasis on the creation of greater collaborations between institutions of higher learning and other key stakeholders to promote the development of prospective teachers’ knowledge of what they will be expected to teach.\r\n